Two patterns in apical dendrite extensions of projection neurons within cerebral cortex of reeler mutant mice - Ryoichi Ichikawa; Ryoichi Ichikawa (Frontiers in Neuroanatomy)
IntroductionPyramidal-like projection neurons in the cerebral cortex exhibit layer-specific positioning of their cell bodies and target specific cortical regions with their apical dendrites. Reeler mutant mice, which lack the gene for the reelin protein gene secreted by Cajal–Retzius cells and have their projection neurons scattered throughout the cortex, display relatively intact global and local neuronal network connections compared with wild-type mice. The irregular morphologies of these cells, which extend their apical dendrites in a neuron-disoriented direction, are thought to compensate for the malposition of the neurons. I aimed to investigate the projection target-specific regulation of this apical dendrite extension pattern in reeler mice.MethodsTo this end, three types of projection neurons–corticospinal (CS), corticothalamic (CT), and corticocallosal (CC) neurons–were evaluated using retrograde labeling techniques.Results and discussionReeler CS neurons displayed a congregation pattern of apical dendritic terminal tips in a specific upper cortical zone, whereas reeler CC neurons exhibited a dispersed pattern of scattered tips throughout the cortex. However, reeler CT neurons showed a hybrid pattern, exhibiting characteristics of both congregation- and dispersion-type neurons. Moreover, apical dendrite extension of these projection neurons follows either a congregation or dispersion mode from postnatal day 0 (P0), which subsequently defines their terminal tip positioning by P8. Thus, this early patterning of apical dendrite arborization in reeler projection neurons likely contributes to the formation of projection target-specific neuronal connections during the first two postnatal weeks.